2022
DOI: 10.1021/acs.jmedchem.2c00951
|View full text |Cite
|
Sign up to set email alerts
|

Screening of a Halogen-Enriched Fragment Library Leads to Unconventional Binding Modes

Abstract: We conceived the Halogen-Enriched Fragment Library (HEFLib) to investigate the potential of halogen bonds in the early stages of drug discovery. As the number of competitive interactions increases with ligand size, we reasoned that a binding mode relying on halogen bonding is more likely for fragments than highly decorated molecules. Thus, fragments could feature unexplored binding modes. We screened the HEFLib against the human kinase DYRK1a and verified micromolar binding fragments via isothermal titration c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…Therefore, it can be argued that the chlorine effect can be useful at all stages of preclinical work, but perhaps with a preference for early preclinical studies. For example, the use of halogen-enriched fragment libraries designed to take advantage of halogen bonding effects has recently been advocated in early hit finding …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it can be argued that the chlorine effect can be useful at all stages of preclinical work, but perhaps with a preference for early preclinical studies. For example, the use of halogen-enriched fragment libraries designed to take advantage of halogen bonding effects has recently been advocated in early hit finding …”
Section: Discussionmentioning
confidence: 99%
“…For example, the use of halogen-enriched fragment libraries designed to take advantage of halogen bonding effects has recently been advocated in early hit finding. 188 This Perspective has attempted to illuminate a concept discussed informally among various medicinal chemistry groups but previously not summarized. The take-home messages are as follows.…”
Section: ■ Conclusion and Outlookmentioning
confidence: 99%
“…The comparable hit rates of HBD count-restricted and nonrestricted fragment sets may partially be due to HBD bioisosterism . Several literature examples have demonstrated that ligand HBDs that form interactions with protein HBA motifs can be successfully replaced with other functional groups, e.g., polarized C– H protons and halogens or sulfur atoms that can form sigma–hole interactions. An interesting example for HBD bioisosterism at the CHK1 kinase hinge motif was reported by Merck scientists: an archetypal donor–acceptor kinase hinge motif in AZD7762 was replaced with a 0 HBD thiazole motif in compound 7 , capable of engaging the hinge via a sulfur-mediated sigma–hole interaction and a nonclassical hydrogen bond through the polarized thiazole C– H proton (Figure ). …”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that this diversity-optimized HEFLib has been thoroughly tested and characterized, resulting in many different hits on various targets. [30][31][32] Another approach for stabilization was identified by covalent modification of cysteines other than C220. 17 A 2-sulfonylpyrimidine was identified that covalently modifies C182 and C277, increasing the T m up to about 2.5 °C without losing affinity towards DNA.…”
Section: Introductionmentioning
confidence: 99%
“…It is noteworthy that this diversity-optimized HEFLib has been thoroughly tested and characterized, resulting in many different hits on various targets. 30–32…”
Section: Introductionmentioning
confidence: 99%